CASE STUDY OF PERMISSIVE PARENTING IN EARLY CHILDHOOD SOCIAL-EMOTIONAL BEHAVIOR - Putri, Karimah Harma; Sadiah Qosyasih, Nelis Nazziatus (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
At an early age all parts of the development that occur in children will experience very rapid development, one of the developmental aspects that need to be given a stimulus is the social-emotional development aspect so that it can regulate emotions and intellectual growth, especially in the field of children's emotional development. This study aims to describe how permissive parenting is applied by parents to children when the process forms patterns of social-emotional behavior in children. Describe how learning and habituation for early childhood. This article uses qualitative research methods. Data collection used a semi-structured interview technique with 2 mothers and one father who had early childhood as respondents. The results of the study revealed that social construction in parents influences the parenting process applied to children. This can be seen from the diversity of parenting methods used by respondents to children.